Transsphenoidal Approach for Sellar Region Tumor : A Case Series - Ibrahim, Sabri; Savitri, Annisa Aulia; Davi, Diqqi (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: Transsphenoidal approaches to the sellar region, with endoscopic or microscopic techniques, are regularly used to treat a diverse collection of pathologies. Case Description: Three patients with presenting symptoms visual disturbance and headache were evaluated with MRI that showes sellar region masses. All patients were undergo transphenoid tumor removal. Post operation evaluation show improvement in visual disturbance and headache with no adverse event after procedure. Discussion : Transsphenoidal endoscopic surgery (TSS) for functional pituitary adenomas yields better endocrinologic results for noninvasive macroadenomas. However, the rate of postoperative CSF leakage was greater with the endoscopic method. In patients with pituitary adenomas, younger age, dense visual field defect, and the preoperative absence of central or bilateral visual field abnormalities were predictive factors of visual field recovery following transsphenoidal approach-tumor excision. Overall survival rates are generally high, ranging from 91% to 98%. Conclusion: Transphenoid approach was a good surgical method for sellar region masses and show good outcomes after operation. Keyword : Sellar region masses; Surgical; Transsphenoid approach Â